Regards croisés sur les Afro-Américains : Mélange en l'honneur de Michel Fabre - Bandry, Michel; Benesch, Klaus; Berben-Masi, Jacqueline; Berrian, Brenda F.; Binder, Wolfgang; Bordat, Francis; Casmier, Stephen; Charras, Françoise; Christol, Hélène; Clary, Françoise; Dantec-Lowry, Hélène Le; Donatien-Yssa, Patricia; et al. (Presses universitaires François-Rabelais, 2017)
In a 1932 article for the journal Opportunity, Charles Hamlin Good acknowledged an earlier “golden age” of African American literature. At the height of the Harlem Renaissance, Good reminded his readers of the writing produced by ante-bellum New Orleans’s Creoles of color. He argued that these writers “deserve more than passing notice for the work they did. In the dark ages of slavery their work foreshadowed the Negro cultural revival of today.” (Good, 79.)
Keywords: History; Literature American; littérature; Africains Américains; histoire; literature; African American; history